2006
DOI: 10.1381/096089206777822296
|View full text |Cite
|
Sign up to set email alerts
|

Weight, Dietary and Physical Activity Behaviors Two Years after Gastric Bypass

Abstract: Postoperative RYGBP patients engage in various weight management behaviors, some of which could offer greater health benefits with follow-up intervention from dietitians and exercise specialists to prevent adverse outcomes such as weight regain and micronutrient deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 24 publications
2
78
1
13
Order By: Relevance
“…Case-controlled studies indicate that bariatric surgery patients have lower levels of physical activity than weight-matched nonsurgery controls (21)(22)(23). A number of retrospective cohort studies report a positive association between physical activity and postsurgery weight loss (24)(25)(26)(27)(28). However, these studies are limited by their observational nature, inclusion of only patients who return for follow-up, and subjectively measured physical activity by self-report questionnaires (29).…”
Section: Resultsmentioning
confidence: 99%
“…Case-controlled studies indicate that bariatric surgery patients have lower levels of physical activity than weight-matched nonsurgery controls (21)(22)(23). A number of retrospective cohort studies report a positive association between physical activity and postsurgery weight loss (24)(25)(26)(27)(28). However, these studies are limited by their observational nature, inclusion of only patients who return for follow-up, and subjectively measured physical activity by self-report questionnaires (29).…”
Section: Resultsmentioning
confidence: 99%
“…É consenso predominante entre investigadores que o critério para avaliação do sucesso no tratamento cirúr-gico da obesidade é a %PEP de pelo menos 50% e a manutenção de peso em longo prazo (13)(14)(15)(16)24). A partir desse critério, as participantes do presente estudo foram divididas e analisadas em três grupos de %PEP: < 50%; 50 ┤75%; ≥ 75%, sendo o primeiro grupo caracterizado como insucesso e os dois outros grupos, como sucesso em relação à perda de peso (13)(14)(15)(16)24).…”
Section: Discussionunclassified
“…Uma perda de peso que se traduz como sucesso cirúrgico deve atingir ao menos 50% do peso excedente no momento da cirurgia (12)(13)(14)(15)(16). Alguns autores estabelecem classificação para sucesso de pós-operatório de acordo com os resultados sobre o índice de massa corporal (IMC), sendo o IMC < 30 kg/m 2 considerado excelente resultado, entre 30 e 35 kg/m 2 , bom resultado e > 35 kg/m 2 , falha ou insucesso (17)(18)(19).…”
unclassified
“…Thus, patients may be likely to return to their unhealthy habits after BS 24 . Silver et al 25 showed that only 17.9% of operated patients were engaged in physical activity after two years since BS, while 82.1% of their sample had a moderate level of physical activity. It reinforced the importance of keeping high PAL to prevent weight regain.…”
Section: Discussionmentioning
confidence: 97%